2016
DOI: 10.1038/ncb3397
|View full text |Cite
|
Sign up to set email alerts
|

NOTCH1 mediates a switch between two distinct secretomes during senescence

Abstract: Senescence, a persistent form of cell cycle arrest, is often associated with a diverse secretome, which provides complex functionality for senescent cells within the tissue microenvironment. We show that oncogene-induced senescence (OIS) is accompanied by a dynamic fluctuation of NOTCH1 activity, which drives a TGF-β-rich secretome, whilst suppressing the senescence-associated pro-inflammatory secretome through inhibition of C/EBPβ. NOTCH1 and NOTCH1-driven TGF-β contribute to ‘lateral induction of senescence’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

37
502
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 421 publications
(541 citation statements)
references
References 67 publications
37
502
1
1
Order By: Relevance
“…Though the mRNA levels of ITGB3 at early timepoints of the induction of senescence were downregulated, we did observe a consistent upregulation of ITGB3 during the establishment of senescence (Figure S3E). This pattern highly resembles the recently described temporal changes induced by NOTCH1 during OIS (Hoare et al., 2016). …”
Section: Resultssupporting
confidence: 88%
“…Though the mRNA levels of ITGB3 at early timepoints of the induction of senescence were downregulated, we did observe a consistent upregulation of ITGB3 during the establishment of senescence (Figure S3E). This pattern highly resembles the recently described temporal changes induced by NOTCH1 during OIS (Hoare et al., 2016). …”
Section: Resultssupporting
confidence: 88%
“…A significant induction of the expression of several other genes encoding SASP components was observed (BMP2, COL3A1, IGFBP5, MMP3, PDGFA, VEGFA; Supporting Information Figure S6c). Interestingly, PDGFA and COL3A1 were recently described as part of the distinct SASP driven by NOTCH1 (Hoare et al, 2016). Furthermore, RXRA knockdown decreased cell proliferation as we observed a drop in the expression of the cell proliferation marker Ki‐67 (Figure 5e and Supporting Information Figure S7) and a decrease in the number of cells (Figure 5f).…”
Section: Resultsmentioning
confidence: 99%
“…In these cells, the SASP develops dynamically and changes its composition in a temporal manner. Within a few hours after entering senescence, the secretome of human somatic fibroblasts is enriched in growth factors and includes transforming growth factor beta‐1 (TGF‐β1) (Hoare et al, 2016; Hubackova, Krejcikova, Bartek, & Hodny, 2012), a cytokine involved in wound healing where it promotes transdifferentiation of fibroblasts into myofibroblasts. After approximately four to six days in senescence, the TGF‐β1‐rich secretome changes as cells begin to secrete pro‐inflammatory cytokines that include interleukin 6 (IL‐6) and 8 (IL‐8) (Hoare et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Within a few hours after entering senescence, the secretome of human somatic fibroblasts is enriched in growth factors and includes transforming growth factor beta‐1 (TGF‐β1) (Hoare et al, 2016; Hubackova, Krejcikova, Bartek, & Hodny, 2012), a cytokine involved in wound healing where it promotes transdifferentiation of fibroblasts into myofibroblasts. After approximately four to six days in senescence, the TGF‐β1‐rich secretome changes as cells begin to secrete pro‐inflammatory cytokines that include interleukin 6 (IL‐6) and 8 (IL‐8) (Hoare et al, 2016). While it is still unclear why the SASP develops in phases, it has been suggested that the temporal evolution of the SASP may be important for orchestrating the distinct stages of tissue repair (Hoare & Narita, 2016; Schmitt, 2016).…”
Section: Introductionmentioning
confidence: 99%